Novel anti-fouling cold-proof garment fabric and process thereof
Phase-change fibers are made by electrospinning and interwoven with the blended fibers. Combined with the hot pressing composite technology of nano titanium dioxide and glass fibers, the existing cold-proof fabrics are easily caught in cold and difficult to clean, and the effects of temperature adjustment, anti-fouling and scratch resistance are achieved.
Patent Information
- Application Number
- CN202510046820.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-13
- Publication Date
- 2025-04-15
AI Technical Summary
Existing cold-proof fabrics are prone to colds due to the heat not easily dissipated during outdoor activities, and it is difficult to keep the clothing clean.
The spinning solution formed by mixing polyethylene glycol and polyvinylpyrrolidone is electrospinned to produce phase-change fibers and interwoven with the blended fibers and insulation fillers to form a fiber cloth. At the same time, nanotitanium dioxide is deposited by vacuum evaporation to form a microporous film, and is hot-pressed and composited with glass fiber cloth to form a three-layer composite clothing fabric.
The fabric can automatically adjust the internal temperature according to changes in the external temperature to maintain a comfortable body temperature. It also has anti-fouling, self-cleaning and scratch-resistant properties, and is suitable for harsh outdoor environments.
Smart Images

Figure CN119820949A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of fabrics and their production, in particular to a production process of clothing fabrics, and also to a novel anti-fouling and cold-proof clothing fabric produced by adopting the process. Background Art
[0002] There are many types of fabrics available, but as people's living standards improve, new types that can meet the needs of different groups of people need to be provided. People's requirements for clothing are not only about clothing style and workmanship, but more about clothing quality, which requires that clothing fabrics should keep up with the development of clothing forms. The characteristics of fabrics such as functionality, comfort, environmental protection, and health have become topics that people are paying more and more attention to.
[0003] Now referring to the invention patent with application number 201810662834.7, the cold-proof fabric disclosed therein is obtained by mixing wool fiber, cashmere fiber, polyvinyl chloride fiber, silk fiber, nylon fiber and cotton and linen fiber. A detailed analysis of the aforementioned patent shows that the patent adopts a method of stacking multiple fibers to achieve a thermal insulation effect of one plus one greater than two. However, the mixture of multiple fiber materials means that when sweating, the heat is not easy to dissipate, which can easily induce cold, which is not conducive to the cold protection needs of outdoor activities. Summary of the invention
[0004] In view of the above-mentioned shortcomings of the prior art, the purpose of the present invention is to provide a new type of anti-fouling and cold-proof clothing fabric and its process to obtain cold-proof, anti-fouling and scratch-resistant fabric, so that clothing made of this fabric can be better used in harsh outdoor environments.
[0005] A manufacturing process of clothing fabrics, comprising the following steps:
[0006] S1: polyethylene glycol and polyvinyl pyrrolidone are mixed in proportion to obtain a spinning solution;
[0007] S2 electrospins the spinning solution to obtain a phase change fiber;
[0008] S3, spinning the phase change fiber and the blended fiber respectively to obtain yarn A and yarn B, taking yarn A, yarn B and thermal insulation filler and blending them on a loom to obtain fiber cloth for later use;
[0009] S4 prepares nano titanium dioxide, and the prepared nano titanium dioxide is deposited by vacuum evaporation to obtain a nano titanium dioxide microporous membrane;
[0010] S5 takes glass fibers and spins and interweaves them to form glass fiber cloth;
[0011] S6 heat-presses and compounds the fiber cloth, the nano-titanium dioxide microporous membrane and the glass fiber cloth to obtain a three-layer composite clothing fabric.
[0012] As a further improvement of the above scheme, polyethylene glycol and polyvinyl pyrrolidone are taken in proportion, polyvinyl pyrrolidone is first dissolved in DMAC solvent, and then polyethylene glycol is added and stirred to obtain spinning solution, the stirring speed is 400-600r / min, and the stirring temperature is 50-60°C. In the present invention, polyvinyl pyrrolidone is dissolved in DMAC solvent to form spinning solution, and polyvinyl pyrrolidone is dispersed in the mixture as a fiber matrix to ensure the formation of nanofibers. In the present invention, polyethylene glycol is added for modification, and polyethylene glycol is used as a phase change component, which has the characteristic of being able to undergo phase change within a temperature range of 5-30°C. The effect of temperature regulation is achieved by polyethylene glycol, specifically: when polyethylene glycol changes from solid to liquid, the molecular structure of polyethylene glycol changes, thereby absorbing heat to overcome the interaction force between molecules, and at this time, heat is stored; when polyethylene glycol changes from liquid to solid, the molecular structure of polyethylene glycol changes again, and the stored heat is released, thereby achieving the purpose of temperature regulation.
[0013] As a further improvement of the above scheme, the specific operation of electrostatic spinning of the spinning solution is as follows: the spinning solution is prepared and electrostatic spinning is performed on an electrostatic spinning machine, the spinning conditions are voltage 5-15KV, injection speed 3-4ml / h, injection distance 90-120mm, and the obtained fiber is washed, oiled and dried. In the present invention, the phase change fiber obtained after polyethylene glycol modification can absorb or release heat when the temperature changes, thereby maintaining a constant temperature. The clothing fabric containing the phase change fiber can automatically adjust the internal temperature according to the change of the external temperature, so as to maintain a comfortable body temperature even in a cold environment.
[0014] As a further improvement of the above scheme, the blended fiber includes rabbit hair fiber, silk fiber and polyester fiber, and the mass ratio of the rabbit hair fiber, silk fiber and polyester fiber is 1 to 5:1 to 3:1.
[0015] As a further improvement of the above solution, the proportion of the heat-insulating filler in the fiber cloth is 5% to 17%, and the heat-insulating filler is any one of expanded cotton, down and foam plastic. In the present invention, heat-insulating filler is added to enhance the cold resistance of the fabric.
[0016] As a further improvement of the above scheme, the method for preparing nano titanium dioxide is specifically performed as follows:
[0017] S41 tetrabutyl titanate and anhydrous ethanol are mixed and stirred to prepare solution A, deionized water and anhydrous ethanol are mixed and nitric acid is added dropwise to adjust the pH value to 3-4 to prepare solution B;
[0018] S42 adding solution A dropwise into solution B at room temperature while stirring, so that solution A and solution B are hydrolyzed and polycondensed to form a light yellow transparent sol;
[0019] S43: drying the sol in a drying oven at 80°C for 24h to form a gel, placing the gel in a high-temperature furnace and heating it to 500°C for heat treatment, and keeping the temperature for 2h to obtain nano titanium dioxide powder. The clothing fabric of the present invention is added with nano titanium dioxide, which can stimulate electron transition under ultraviolet light irradiation to form electron-hole pairs with strong redox ability, so that it can react with water molecules and oxygen molecules to generate hydroxyl radicals and superoxide anion radicals with strong oxidizing properties, thereby degrading organic pollutants on the fabric to keep the surface of the fabric clean, and the photocatalytic effect of nano titanium dioxide can cause photodegradation of organic matter, giving the fabric anti-fouling and self-cleaning properties, and also improving the ultraviolet protection performance of the fabric, so that it is more suitable for use in outdoor severe cold environments.
[0020] As a further improvement of the above scheme, the method for treating nano titanium dioxide powder by vacuum evaporation deposition is specifically operated as follows: disperse the nano titanium dioxide powder in a polyethylene aqueous solution, transfer it into a vacuum heating, heat and evaporate the mixed solution, and vaporize it in a substrate to obtain a nano titanium dioxide microporous membrane. The present invention prepares nano titanium dioxide into a microporous membrane by vacuum evaporation deposition, and introduces it into clothing fabrics by combining hot pressing technology, and uses it as a surface layer to play a self-cleaning role, thereby giving the clothing fabrics an anti-fouling effect.
[0021] As a further improvement of the above scheme, glass fiber cloth is laid between the fiber cloth and the nano-titanium dioxide microporous membrane to form a stacked cloth blank, and the stacked cloth blank is input into a hot press and hot-pressed for 15 to 30 seconds at a temperature of 110 to 120° C. to obtain a three-layer composite clothing fabric.
[0022] A novel anti-fouling and cold-proof clothing fabric comprises the following components by weight: 30-60 parts of blended fibers, 6-10 parts of thermal insulation fillers, 11-20 parts of polyethylene glycol, 15-30 parts of polyvinyl pyrrolidone, 10-18 parts of nano titanium dioxide and 8-14 parts of glass fibers.
[0023] As a further improvement of the above scheme, the clothing fabric has an inner layer, an intermediate layer and an outer layer, wherein the blended fiber, thermal insulation filler, polyethylene glycol and polyvinyl pyrrolidone are mixed in a ratio of 3-10:1:1-4:1.5-5 to make the inner layer, nano titanium dioxide is subjected to vacuum evaporation deposition to form the outer layer, and glass fiber is spun to form the intermediate layer. In the present invention, the added glass fiber has high strength, high modulus and good corrosion resistance. As a reinforcing layer, after being spun to form a glass fiber cloth, it is hot-pressed and compounded on the outermost side of the fabric, which enhances the wear and scratch resistance of the fabric and can be better applied to outdoor environments.
[0024] Compared with the prior art, the present invention has the following beneficial effects:
[0025] The present invention introduces polyethylene glycol for modification. The phase change fiber obtained after polyethylene glycol modification can absorb or release heat when the temperature changes, thereby maintaining a constant temperature. The clothing fabric containing the phase change fiber can automatically adjust the internal temperature according to the change of the external temperature, thereby maintaining a comfortable body temperature even in a cold environment. In addition, nano titanium dioxide is added to give the fabric anti-fouling and self-cleaning properties, and also improves the ultraviolet protection performance of the fabric, so that it is more suitable for use in outdoor severe cold environments.
[0026] The production process of the present invention uses a spinning solution formed by mixing polyethylene glycol and polyvinyl pyrrolidone to perform electrostatic spinning to obtain phase change fibers, and a fiber cloth formed by interweaving thermal insulation fillers and blended fibers as an inner layer, a nanofilm formed by depositing nano titanium dioxide by vacuum evaporation as an intermediate layer, and a glass fiber cloth formed by spinning glass fibers as an outer layer. The three layers are hot-pressed and composited to obtain clothing fabrics. The clothing fabrics have the advantages of cold resistance, stain resistance and scratch resistance, and can be better suitable for use in harsh environments. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 Shown is a flow chart of a manufacturing process of a clothing fabric provided by the present invention. DETAILED DESCRIPTION
[0028] In order to make the purpose, technical scheme and advantages of the present invention clearer, the present invention is further described in detail below in conjunction with the embodiments. Additional aspects and advantages of the present invention will be given in part in the following description, and will become apparent from the following description, or will be understood through the practice of the present invention. It should be understood that the following description is only used to explain the present invention and is not intended to limit the present invention.
[0029] As used herein, the terms "comprises," "including," "contains," or any other variation thereof, are intended to cover a non-exclusive inclusion. For example, a composition, process, method, article, or apparatus that comprises the listed elements is not necessarily limited to only those elements but may include other elements not expressly listed or inherent to such composition, process, method, article, or apparatus.
[0030] When an amount, concentration, or other value or parameter is expressed as a range, a preferred range, or a range limited by a series of upper preferred values and lower preferred values, this should be understood as specifically disclosing all ranges formed by any pairing of any range upper limit or preferred value with any range lower limit or preferred value, regardless of whether the range is disclosed separately. For example, when a range of "1 to 5" is disclosed, the described range should be interpreted as including a range of "1 to 4", "1 to 3", "1 to 2", "1 to 2 and 4 to 5", "1 to 3 and 5" etc. When a numerical range is described in this article, unless otherwise specified, the range is intended to include its end values and all integers and fractions within the range.
[0031] The specific embodiments of the present invention are described in detail below.
[0032] Example 1
[0033] This embodiment provides a new type of anti-fouling and cold-proof clothing fabric, which is composed of the following parts by weight: 30 parts of blended fiber, 6 parts of down, 12 parts of polyethylene glycol, 18 parts of polyvinyl pyrrolidone, 10 parts of nano titanium dioxide, and 8 parts of glass fiber. The clothing fabric has an inner layer, an intermediate layer and an outer layer, wherein the blended fiber, thermal insulation filler, polyethylene glycol and polyvinyl pyrrolidone are mixed in a ratio of 5:1:2:3 to make the inner layer, and rabbit hair fiber, silk fiber and polyester fiber are mixed in a ratio of 1:1:1 to make the blended fiber. Nano titanium dioxide is vacuum evaporated and deposited to form the outer layer, and glass fiber is spun to form the intermediate layer.
[0034] The manufacturing process of the clothing fabric of this embodiment includes the following steps:
[0035] S1: Take 12 parts of polyethylene glycol and 18 parts of polyvinyl pyrrolidone, first dissolve the polyvinyl pyrrolidone in DMAC solvent, then add polyethylene glycol and stir to obtain spinning solution, the stirring speed is 500 r / min, and the stirring temperature is 55°C.
[0036] S2 Phase change fiber obtained by electrospinning the spinning solution: The prepared spinning solution is electrospun on an electrospinning machine. The spinning conditions are voltage 10KV, injection speed 4ml / h, injection distance 120mm. The obtained fiber is washed, oiled and dried.
[0037] S3 spins the phase change fiber and the blended fiber separately to obtain yarn A and yarn B, takes yarn A, yarn B and thermal insulation filler and blends and interweaves them on a loom to obtain fiber cloth for standby use, wherein the thermal insulation filler accounts for 10% of the fiber cloth.
[0038] S4 prepares nano titanium dioxide, takes 10 parts of nano titanium dioxide and deposits them by vacuum evaporation to obtain a nano titanium dioxide microporous membrane.
[0039] The method for preparing nano titanium dioxide is specifically performed as follows:
[0040] S41 tetrabutyl titanate and anhydrous ethanol were mixed and stirred to prepare solution A, deionized water and anhydrous ethanol were mixed and nitric acid was added dropwise to adjust the pH value to 3 to prepare solution B.
[0041] S42 Solution A is added dropwise into solution B at room temperature while stirring, and solution A and solution B are hydrolyzed and polycondensed to form a light yellow transparent sol.
[0042] S43: Dry the sol in a drying oven at 80°C for 24 hours to form a gel, place the gel in a high-temperature furnace and heat it to 500°C for heat treatment, and keep it warm for 2 hours to obtain nano titanium dioxide powder.
[0043] The vacuum evaporation deposition method for treating nano titanium dioxide powder is specifically performed as follows: dispersing the nano titanium dioxide powder in a polyethylene aqueous solution, moving it into a vacuum heating process, heating and evaporating the mixed solution, and vaporizing it in a substrate to obtain a nano titanium dioxide microporous membrane.
[0044] S5 takes 8 parts of glass fibers and spins and interweaves them to form glass fiber cloth.
[0045] S6: laying the glass fiber cloth between the fiber cloth and the nano-titanium dioxide microporous membrane to form a stacked cloth blank, inputting the stacked cloth blank into a hot press, and hot pressing for 18 seconds at a temperature of 120° C. to obtain a three-layer composite clothing fabric.
[0046] Example 2
[0047] This embodiment provides a new type of anti-fouling and cold-proof clothing fabric, which is composed of the following parts by weight: 50 parts of blended fiber, 8 parts of down, 18 parts of polyethylene glycol, 26 parts of polyvinyl pyrrolidone, 16 parts of nano titanium dioxide, and 12 parts of glass fiber. The clothing fabric has an inner layer, an intermediate layer and an outer layer, wherein the blended fiber, thermal insulation filler, polyethylene glycol and polyvinyl pyrrolidone are mixed in a ratio of 6.25:1:2.25:3.25 to make the inner layer, and rabbit hair fiber, silk fiber and polyester fiber are mixed in a ratio of 4:2:1 to obtain the blended fiber. Nano titanium dioxide is vacuum evaporated and deposited to form the outer layer, and glass fiber is spun to form the intermediate layer.
[0048] The manufacturing process of the clothing fabric of this embodiment includes the following steps:
[0049] S1: Take 18 parts of polyethylene glycol and 26 parts of polyvinyl pyrrolidone, first dissolve the polyvinyl pyrrolidone in DMAC solvent, then add polyethylene glycol and stir to obtain spinning solution, the stirring speed is 500 r / min, and the stirring temperature is 55°C.
[0050] S2 Phase change fiber obtained by electrospinning the spinning solution: The prepared spinning solution is electrospun on an electrospinning machine. The spinning conditions are voltage 10KV, injection speed 4ml / h, injection distance 120mm. The obtained fiber is washed, oiled and dried.
[0051] S3 performs spinning treatment on the phase change fiber and the blended fiber respectively to obtain yarn A and yarn B, and takes yarn A, yarn B and thermal insulation filler and blends and interweaves them on a loom to obtain fiber cloth for standby use. The thermal insulation filler accounts for 8.5% of the fiber cloth.
[0052] S4 prepares nano titanium dioxide, takes 16 parts of nano titanium dioxide and deposits them by vacuum evaporation to obtain a nano titanium dioxide microporous membrane.
[0053] The method for preparing nano titanium dioxide is specifically performed as follows:
[0054] S41 tetrabutyl titanate and anhydrous ethanol were mixed and stirred to prepare solution A, deionized water and anhydrous ethanol were mixed and nitric acid was added dropwise to adjust the pH value to 3 to prepare solution B.
[0055] S42 Solution A is added dropwise into solution B at room temperature while stirring, and solution A and solution B are hydrolyzed and polycondensed to form a light yellow transparent sol.
[0056] S43: Dry the sol in a drying oven at 80°C for 24 hours to form a gel, place the gel in a high-temperature furnace and heat it to 500°C for heat treatment, and keep it warm for 2 hours to obtain nano titanium dioxide powder.
[0057] The vacuum evaporation deposition method for treating nano titanium dioxide powder is specifically performed as follows: dispersing the nano titanium dioxide powder in a polyethylene aqueous solution, moving it into a vacuum heating process, heating and evaporating the mixed solution, and vaporizing it in a substrate to obtain a nano titanium dioxide microporous membrane.
[0058] S5 takes 12 parts of glass fibers and spins and interweaves them to form glass fiber cloth.
[0059] S6: laying the glass fiber cloth between the fiber cloth and the nano-titanium dioxide microporous membrane to form a stacked cloth blank, inputting the stacked cloth blank into a hot press, and hot pressing for 18 seconds at a temperature of 120° C. to obtain a three-layer composite clothing fabric.
[0060] Example 3
[0061] This embodiment provides a new type of anti-fouling and cold-proof clothing fabric, which is composed of the following parts by weight: 60 parts of blended fiber, 10 parts of down, 20 parts of polyethylene glycol, 30 parts of polyvinyl pyrrolidone, 18 parts of nano titanium dioxide, and 14 parts of glass fiber. The clothing fabric has an inner layer, an intermediate layer and an outer layer, wherein the blended fiber, thermal insulation filler, polyethylene glycol and polyvinyl pyrrolidone are mixed in a ratio of 6:1:2:3 to make the inner layer, and rabbit hair fiber, silk fiber and polyester fiber are mixed in a ratio of 5:3:1 to make the blended fiber. Nano titanium dioxide is vacuum evaporated and deposited to form the outer layer, and glass fiber is spun to form the intermediate layer.
[0062] The manufacturing process of the clothing fabric of this embodiment includes the following steps:
[0063] S1: Take 20 parts of polyethylene glycol and 30 parts of polyvinyl pyrrolidone, first dissolve the polyvinyl pyrrolidone in DMAC solvent, then add polyethylene glycol and stir to obtain spinning solution, the stirring speed is 500 r / min, and the stirring temperature is 55°C.
[0064] S2 Phase change fiber obtained by electrospinning the spinning solution: The prepared spinning solution is electrospun on an electrospinning machine. The spinning conditions are voltage 10KV, injection speed 4ml / h, injection distance 120mm. The obtained fiber is washed, oiled and dried.
[0065] S3 spins the phase change fiber and the blended fiber separately to obtain yarn A and yarn B, takes yarn A, yarn B and thermal insulation filler and blends and interweaves them on a loom to obtain fiber cloth for standby use, wherein the thermal insulation filler accounts for 9.1% of the fiber cloth.
[0066] S4 prepares nano titanium dioxide, takes 18 parts of nano titanium dioxide and deposits it by vacuum evaporation method to obtain nano titanium dioxide microporous membrane.
[0067] The method for preparing nano titanium dioxide is specifically performed as follows:
[0068] S41 tetrabutyl titanate and anhydrous ethanol were mixed and stirred to prepare solution A, deionized water and anhydrous ethanol were mixed and nitric acid was added dropwise to adjust the pH value to 3 to prepare solution B.
[0069] S42 Solution A is added dropwise into solution B at room temperature while stirring, and solution A and solution B are hydrolyzed and polycondensed to form a light yellow transparent sol.
[0070] S43: Dry the sol in a drying oven at 80°C for 24 hours to form a gel, place the gel in a high-temperature furnace and heat it to 500°C for heat treatment, and keep it warm for 2 hours to obtain nano titanium dioxide powder.
[0071] The vacuum evaporation deposition method for treating nano titanium dioxide powder is specifically performed as follows: dispersing the nano titanium dioxide powder in a polyethylene aqueous solution, moving it into a vacuum heating process, heating and evaporating the mixed solution, and vaporizing it in a substrate to obtain a nano titanium dioxide microporous membrane.
[0072] S5 takes 14 parts of glass fibers and spins and interweaves them to form glass fiber cloth.
[0073] S6: laying the glass fiber cloth between the fiber cloth and the nano-titanium dioxide microporous membrane to form a stacked cloth blank, inputting the stacked cloth blank into a hot press, and hot pressing for 18 seconds at a temperature of 120° C. to obtain a three-layer composite clothing fabric.
[0074] Example 4
[0075] The difference between this embodiment and embodiment 2 is that in this embodiment, polyethylene glycol and polyvinyl pyrrolidone are not added, and the rest is the same as embodiment 2.
[0076] Example 5
[0077] The difference between this embodiment and embodiment 2 is that in this embodiment, nano titanium dioxide is not added, and the rest is the same as embodiment 2.
[0078] Next, the thermal insulation effect of the fabric is evaluated by testing its heat transfer performance. The test method adopts the thermal resistance method, and the cold-proof performance of the fabrics of Examples 1-4 is tested according to the national standard GB / T "Fabric Thermal Resistance Test Method". The test results show that the thermal resistance values of the fabrics of Examples 1 to 3 are significantly greater than that of Example 4, and the thermal resistance values measured in Examples 1 to 3 increase successively, and the higher the value, the better it can prevent heat conduction and provide better thermal insulation and cold-proof effects. This proves that the invention introduces polyethylene glycol for modification, so that the cold-proof performance of the prepared clothing fabrics is significantly improved.
[0079] According to the provisions of GB / T8629-2001, the fabrics of Examples 1-3 and 5 were tested for anti-fouling ability. The test results show that when the initial color difference of the fabrics of Examples 1 to 3 is equal to or higher than level 3-4, the color difference level of the test results is 2 levels higher than the initial color difference, and the initial color difference of the fabric of Example 5 is less than 2 levels, and the color difference level of the test results and the initial color difference do not change. When the initial color difference is equal to or higher than level 3-4, the color difference level of the test results is higher than the initial color difference by 0.5 levels or more, and it is considered that the sample has easy decontamination, which proves that the present invention, the introduction of nano titanium dioxide, improves the anti-fouling performance of the fabric.
[0080] The above embodiments are merely preferred implementations of the present invention. Any simple modification, amendment and substitution of the above embodiments based on the technical essence of the present invention shall fall within the scope of the technical solution of the present invention.
Claims
1. A process for producing clothing fabrics, characterized in that: The following steps are involved: S1: polyethylene glycol and polyvinyl pyrrolidone are mixed in proportion to obtain a spinning solution; S2 electrospins the spinning solution to obtain a phase change fiber; S3, spinning the phase change fiber and the blended fiber respectively to obtain yarn A and yarn B, taking yarn A, yarn B and thermal insulation filler and blending them on a loom to obtain fiber cloth for later use; S4 prepares nano titanium dioxide, and the prepared nano titanium dioxide is deposited by vacuum evaporation to obtain a nano titanium dioxide microporous membrane; S5 takes glass fibers and spins and interweaves them to form glass fiber cloth; S6 heat-presses and compounds the fiber cloth, nano-titanium dioxide microporous membrane and glass fiber cloth to obtain a three-layer composite clothing fabric.
2. The manufacturing process according to claim 1, characterized in that: Polyethylene glycol and polyvinyl pyrrolidone are taken in proportion, polyvinyl pyrrolidone is first dissolved in DMAC solvent, and then polyethylene glycol is added and stirred to obtain spinning solution, the stirring speed is 400-600 r / min, and the stirring temperature is 50-60°C.
3. The manufacturing process according to claim 1, characterized in that: The specific operation of electrospinning the spinning solution is as follows: the prepared spinning solution is electrospinned on an electrospinning machine under the spinning conditions of voltage 5-15KV, injection speed 3-4ml / h, injection distance 90-120mm, and the obtained fiber is washed, oiled and dried.
4. The manufacturing process according to claim 1, characterized in that: The blended fibers include rabbit hair fibers, silk fibers and polyester fibers, and the weight ratio of the rabbit hair fibers, silk fibers and polyester fibers is 1 to 5:1 to 3:
1.
5. The manufacturing process according to claim 4, characterized in that: The thermal insulation filler accounts for 5% to 17% of the fiber cloth; The heat-insulating filler is any one of expanded cotton, down and foam plastic.
6. The manufacturing process according to claim 1, characterized in that: The method for preparing nano titanium dioxide is specifically performed as follows: S41 tetrabutyl titanate and anhydrous ethanol are mixed and stirred to prepare solution A, deionized water and anhydrous ethanol are mixed and nitric acid is added dropwise to adjust the pH value to 3-4 to prepare solution B; S42 adding solution A dropwise into solution B at room temperature while stirring, so that solution A and solution B are hydrolyzed and polycondensed to form a light yellow transparent sol; S43: Dry the sol in a drying oven at 80°C for 24 hours to form a gel, place the gel in a high-temperature furnace and heat it to 500°C for heat treatment, and keep it warm for 2 hours to obtain nano titanium dioxide powder.
7. The manufacturing process according to claim 6, characterized in that: The vacuum evaporation deposition method for treating nano titanium dioxide powder is specifically performed as follows: dispersing the nano titanium dioxide powder in a polyethylene aqueous solution, moving it into a vacuum heating process, heating and evaporating the mixed solution, and vaporizing it in a substrate to obtain a nano titanium dioxide microporous membrane.
8. The manufacturing process according to claim 1, characterized in that: The glass fiber cloth is laid between the fiber cloth and the nano-titanium dioxide microporous membrane to form a stacked cloth blank, and the stacked cloth blank is input into a hot press machine and hot-pressed for 15 to 30 seconds at a temperature of 110 to 120° C. to obtain a three-layer composite clothing fabric.
9. A new type of anti-fouling and cold-proof clothing fabric, characterized in that: The clothing fabric is composed of the following parts by weight: 30-60 parts of blended fibers, 6-10 parts of thermal insulation fillers, 11-20 parts of polyethylene glycol, 15-30 parts of polyvinyl pyrrolidone, 10-18 parts of nano titanium dioxide, and 8-14 parts of glass fibers.
10. The novel anti-fouling and cold-proof clothing fabric according to claim 9, characterized in that: The clothing fabric comprises an inner layer, a middle layer and an outer layer, wherein the inner layer is made by mixing blended fibers, thermal insulation fillers, polyethylene glycol and polyvinyl pyrrolidone in a ratio of 3-10:1:1-4:1.5-5; the outer layer is formed by vacuum evaporation deposition of nano-titanium dioxide, and the middle layer is formed by spinning glass fibers; The clothing fabric is manufactured by using the manufacturing process described in any one of claims 1 to 8.
Citation Information
Patent Citations
Cold-proof fabric
CN108796763A
Nano photocatalytic clothing material and preparation method thereof
CN102771921A
Composite phase-change nano-fiber material and preparation method thereof
CN108754661A
Nanometer self-cleaning fabric and production method thereof
CN108823966A
Production method of fibers for antibacterial and durable mattress fabric
CN110359109A
Cited By
Preparation method of laminated flame-retardant polymer composite waterproof coiled material
CN121268354A